2011
DOI: 10.4172/2157-7064.1000109
|View full text |Cite
|
Sign up to set email alerts
|

RP-HPLC Method for Simultaneous Determination of Captopril and Diuretics: Application in Pharmaceutical Dosage Forms and Human Serum

Abstract: An isocratic reversed phase high-performance liquid chromatographic (RP-HPLC) method has been developed for the simultaneous determination of captopril and diuretics (furosemide and hydrochlorothiazide) in API, dosage formulations and human serum. Chromatographic separation was achieved on Purospher Start C18 (250 mm x 4.6 mm, 5 μm) and Hypersil ODS C18 (150×4.6mm, 5micron) columns using mobile phase, methanol: water (70:30 v/v) adjusted to pH 3.0 via phosphoric acid 85% having flow rate of 1.0 mL min-1 at amb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Harlikar et al (2003) have reported simultaneous determination of a few ACE-inhibitors like perindopril, ramipril and trandolapril along with indapamide. Sultana et al (2010Sultana et al ( , 2011 and El-Gindy et al (2013) reported the analysis of captopril, indapamide and related compounds using HPLC. Other methods utilizing HPLC for simultaneous determination of ACE-Inhibitors were reported by Bonazzi et al (1997) and Manna et al (2001).…”
Section: Captoprilmentioning
confidence: 99%
“…Harlikar et al (2003) have reported simultaneous determination of a few ACE-inhibitors like perindopril, ramipril and trandolapril along with indapamide. Sultana et al (2010Sultana et al ( , 2011 and El-Gindy et al (2013) reported the analysis of captopril, indapamide and related compounds using HPLC. Other methods utilizing HPLC for simultaneous determination of ACE-Inhibitors were reported by Bonazzi et al (1997) and Manna et al (2001).…”
Section: Captoprilmentioning
confidence: 99%
“…The solution from the extraction (20 mL) was injected to HPLC by chromatographic conditions chosen using C18 column (250 × 4.6 mm, 5 µm), UV-Vis detector [11]. Measurements were taken at 0, 0.5, 1, 1.5, 2, 2.5, 3, 4, 8, and 10 hrs after administration of the furosemide.…”
Section: Examination Of Furosemide Levels In the Bloodmentioning
confidence: 99%
“…Our research colleagues have reported a number of liquid chromatographic methods with UV detection for different classes of simultaneously prescribed drugs including statins [26], NSAIDs [27], diuretics [28], ACE inhibitors [29], quinolones [30], H 1 -receptor antagonists [31], H 2 -receptor antagonists [32], anti-diabetic [33] drugs and so on. Almost, all of these methods have been developed and validated isocratically at isobestic point of studied drugs.…”
Section: Introductionmentioning
confidence: 99%